ชาติพันธุ์นิพนธ์: การศึกษาเชิงอัตชีวประวัติผ่านมุมมอง ทัศนคติของม้าทรงเทพเจ้าจีนในสามจังหวัดทางภาคใต้ของประเทศไทย - Tirapalika, Benjarong (RUSAMILAE JOURNAL, 2022)
Instead than describing mediums from the standpoint of rituals, beliefs, and uncontrollable minds, the main goal of this essay is to try an auto ethnographic study of a group of mediums living there. visited the southern regions to learn about the way of life, the attitudes of people, and what a medium genuinely looks like. The study’s findings demonstrated that although cultures surrounding mediums attempt to frame the spirits that take on the roles of Chinese gods during festivals, they are nevertheless required to behave according to their own customs. The medium is similar to how many societal groupings live their lives. The inability of the medium to act appropriately under the circumstances of the medium might be caused by happy, happy, sad, or even many other things. Moreover, Additionally, this ethnography discovers that the members of the medium are attempting to convince outsiders that they are neither supernatural nor charming as previously thought.